Survival Analysis in Elderly Patients with Glioblastomas: The Influence of Clinical Status, Tumor and Surgical Features - Sousa, Ulysses Oliveira; Oliveira, Matheus Fernandes; Heringer, Lindolfo Carlos; Botelho, Ricardo Vieira; Rotta, José Marcus (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Introduction Glioblastomas are malignant neoplasms, notorious for their poor prognosis. We have conducted a survival analysis in a sample of elderly patients with glioblastomas.Methods The sample of the present study consisted of elderly patients consecutively admitted from January 2014 to January 2016 (24 months) at the Hospital do Servidor Público Estadual de São Paulo. We have evaluated the impact of age, Karnofsky scale (KS) score, tumor location, and occurrence of perioperative complications.Results A total of 42 patients were analyzed. Of these, 23 (54.7%) were men, and 19 (45.3%) were women. Patients > 60 years old, with low KS score, deep-seated tumors, and those with perioperative complications had worst outcomes.Discussion and conclusion Surgery, perioperative chemotherapy and radiotherapy add survival time and quality of life to these patients. In patients with low KS score, isolated radiotherapy and/or chemotherapy might be adequate. Decreasing perioperative complications is essential to adequately deliver adjuvant therapy in elderly patients.
Keywords: neoplasms; glioblastoma; prognosis